(3SJI YTQ cjdh eJQGs (3QhGjIs - (3SeGf, fGaPs; (3GdYQHj, MSfs; (3SjdG, cGJQjfGs; (3efJUQ, eQjes ((3GdbGgQIs (3OGQ GdafGQs, 2023)
(3dG COQj eJi YOJ deeGQSI OhQj ceSDhd Yf UZGQj, hdcf dGHO Cf GdCeQ bO JWdH hbkJG djS HbUjQ, HOCoJ TjkFG aTjkFG CTYQ HYOe GQJHGWj HCqj TjA, HOCoJ CHJYO Yf GdefGbTGJ hGdSgQGJ Hd hMJi GdeLGedGJ, HOCJ CQcf CcKQ ddhMOI hGdUeJ, de jYO jYfjfj eG jLQj NGQL LOQGf efRdj, hde CYO CfGbT Ch CYJQV Ydi CSYGQ GdSdY Ch MJi SGYGJ GfbWGY GdcgQHGA, HOCJ LpqOkjG CacQ HGdgLQI Ch HGdgQhH CkqjG cGfJ GdJSejI, EdG Cffj HOCJ CTYQ HCf Ydqj Cf CJQc gPG GdecGf, hEdG agh SjHJdYfj dG Tc, HOCoJ oCSpqNa bhd OQhjT (B: (S0(3Ydi gPg GdCQV eG jSJMb GdMjGI(S1(B.. (3hHOC jSjWQ Ydnqj bhd GdeGZhW(B: (S0(3dG TjA jQHWfj HgPg GdCQV Shi GdMPGA(S1(B.. (3cja SCQMd hEdi Cjf?s
(3GdMGUdI Ydi LGFRI (B(samlagpris) (3GdTgjQIs
Keywords: (3GdbUU GdYQHjIs -- (3eUQs